Hubungan Night Time Eating dan Asupan Lemak Dengan Kejadian Gizi Lebih Pada Mahasiswa di Kota Medan: The Association Between Night Time Eating, Fat Intake, and The Incidence of Overweight Among University Students in Medan City - Sandy, Yatty; Rukmana, Erni; Damanik, Kanaya Yori; Pratiwi, Caca (Universitas Airlangga, 2024)
Background: University students are the age group of late adolescents who are still undergoing growth and development. Growth and development must be supported by balanced nutritional intake and healthy eating habits. Currently, an emerging trend is that numerous campus activities and academic demands often lead students to develop nighttime eating habits, typically involving high-fat foods, outside of regular mealtimes. Objectives: To determine the relationship between nighttime eating, fat intake, and the incidence of overweight among college students. Methods: The research design was cross-sectional, with purposive sampling technique. A total of 106 students, aged 19-23 years, participated in this study. The instruments used included the Night Eating Diagnostic Questionnaire (NEDQ) to assess night eating habits, a 24-hour food recall questionnaire to estimate fat intake, weight scales and microtoice to calculate Body Mass Index and determine nutritional status. Data analysis was conducted using chi-square and logistic regression. Results: There was a relationship between night time eating and the incidence of overnutrition (p-value = 0.040). There was also a significant relationship between fat intake and the incidence of overweight (p-value = 0.005) among college students. The results further indicate that adolescents with nighttime eating are 3.785 times more likely to being overweight. Additionally, adolescents with high fat intake are 3,814 times more likely to be overnourished. Conclusions: Eating habits and nutritional intake are crucial to create healthy and productive adolescents.